Evaluation of the Patient Profile and Current Pattern of Care with Docetaxel Based Adjuvant Regimen in Operable Breast Cancer - Hai, MA; Akhter, Parveen Shahida; Chowdhury, Quamruzzaman; Banu, Parvin Akhter; Hossain, Mofazzel; Pervin, Kumkum (Delta Medical College Journal, 2019)
Background: Early stage breast cancer can often be cured with surgery alone though there are chances of recurrent disease and decrease in survival. Adjuvant poly-chemotherapy with docetaxel-based regimens can improve both disease-free and overall survival in patients with operable breast cancer. Objective: This study was designed to evaluate the patient profile and current pattern of care with docetaxel based adjuvant regimen in operable breast cancer patients including the treatment outcome from clinical practice. Materials and method: This prospective, observational, non-comparative study planned to enroll newly diagnosed operable breast cancer patients with high risk of recurrence after surgery. Selection of docetaxel-based treatment strategy and dosage of therapy was at the discretion of individual oncologists as per routine clinical practice. Patient data were recorded during inclusion, each cycle of therapy, and follow-up at 1 year (+/- 1 month) after inclusion. Results: Between August 2008 and July 2011 a total of 85 patients with median age of 53 years (23-73 years) were enrolled and 53 (62.4%) patients were postmenopausal. Ductal carcinoma, the most common cancer type,was found in 73 (85.9%) patients. Receptor status was positive for estrogen, progesterone or Her2/neu/erbB2 in 65.9%, 47.1% and 5.8% patients, respectively. Mastectomy either partial or total was performed in 76 (89.4%) patients for the current disease. An average of 8 (range: 2-15) lymph nodes (LN) mostly in axilla were excised in 56 patients and average of 4 (range: 1-11) LN nodes were positive. Sentinel LNs were negative, excised in 4 patients. The mean tumor size was 5.5 cm and most (82.4%) patients were diagnosed at Stage II disease including some at Stage I and III (7.1%, 10.6%). Docetaxel (Taxotere®) was combined with cyclophosphamide alone or in addition with doxorubicin, epirubicin, 5 FU and trastuzumab either in combination or sequential regimen. Taxotere in combination with adriamycin and cyclophosphamide was planned for 63.5% patients. Trastuzumab as sequential therapy could be afforded by 1 patient only. Data regarding radiotherapy or hormone therapy was not recorded. At the end of four cycles, 83.5% of patients were found disease free and 5.9% had loco regional relapse. At 1 year 71 (93.4%) patients were alive, 63 (88.7%) were relapse-free and 8 (11.2%) had loco regional relapse. Nausea, vomiting, diarrhea, alopecia, anemia and neutropenia were most commonly reported adverse events classified as Grade 1 or Grade 2. Grade 3 neutropenia was reported in 5 patients and 2 patients reported grade 4 neutropenia. Grade 3 diarrhea was reported in 1 patient. Conclusion: Docetaxel as adjuvant chemotherapy offered one year survival in 93.4% (71/76) of the patients and 88.7% (63/71 patients) were disease-free. The safety profile of docetaxel based regimens was expected and manageable. Delta Med Col J. Jan 2019 7(1): 4-10